Effects of the Low-Dose Colchicine Regimen on Left Ventricular Adverse Remodeling and Systolic Function in Acute Myocardial Infarction Patients With Anterior ST Segment Elevation Undergoing Primary Percutaneous Coronary Intervention: A Randomized Controlled Trial - Caesario, Fahreza; Prasetya, Indra; Rohman, Mohammad Saifur; satrijo, Budi; Anjarwani, Setyasih (Heart Science Journal, 2024)
Background: Inflammation in reperfusion injury results in adverse ventricular remodeling and reduced systolic function. The anti-inflammatory effects of colchicine have shown beneficial effects in cardiovascular disease.Objective: To determine the effects of low-dose colchicine on left ventricular (LV) adverse remodeling and systolic function in acute myocardial infarction with anterior ST-segment elevation (anterior STEMI) patients undergoing primary percutaneous coronary intervention (PPCI).Material and Methods: This prospective, randomized, double-blinded study randomly assigned anterior STEMI patients who underwent PPCI to receive either low-dose colchicine (1mg loading dose followed by 0.5mg daily) or a matching placebo for 30 days in addition to standard therapy. Outcomes included adverse LV remodeling and systolic function, determined by transthoracic echocardiography (TTE) in the first and third month.Result: Enrollment comprised 196 patients, with 92 patients in the colchicine group and 104 patients in the placebo group. Adverse LV remodeling and a decrease in systolic function were observed in both groups. No significant differences in LV remodeling were observed between the colchicine and placebo groups, as indicated by the change in LV end-systolic volume index (LVESVI) at the first month (16.5% vs. 18.25% [p=0.091]) and third month (19.5% vs. 21.5% [p=0.124]). Similar results were found in LV systolic function between the colchicine and placebo groups, with a reduction in LV ejection fraction (LVEF) observed in the first month (6.3% vs. 8.95% [p=0.083]) and third month (9.5% vs. 11.5% [p=0.163]). Diarrhea was the only reported side effect, occurring in 6.5% of patients in the colchicine group.Conclusion: Low-dose colchicine administration in anterior STEMI patients undergoing PPCI did not reduce LV adverse remodeling or systolic function.